Genotoxic Potentials of Varieties of Cassava (Manihot esculenta) in the Uptake of Heavy Metals from Vehicular Emission (Lead, Arsenic, Chromium, Cadmium, and Zinc): A Review - Fami, Pakka E.; Yaro, Amos J. T.; E., M. Alahira; H., Sonka S. (Darul Yasin Al Sys, 2025)
Cassava (Manihot esculenta) is a widely consumed staple crop, with numerous species cultivated for their agronomic traits such as yield, tuber size, and color. These species—including TMS90257, TMS84537, TMS82/00056, TMS82/00661, NR8212, NR8082, TMS50395, and TMS30555—are generally classified into three groups based on hydrocyanic acid concentration. This review investigates the genotoxic potential of various Manihot esculenta species in relation to their capacity to uptake harmful heavy metals from the soil. The primary sources of metal contamination examined are agrochemicals, particularly pesticides, and vehicular emissions. The review synthesizes findings from existing literature indicating that while cassava absorbs heavy metals such as lead, arsenic, cadmium, chromium, and zinc, the concentrations in most cases remain within World Health Organization (WHO) permissible limits. However, continued exposure to these elements poses significant health risks due to their cumulative toxic effects. The study underscores the importance of educating farmers and consumers about the implications of heavy metal uptake in food crops and advocates for stricter monitoring and awareness to mitigate potential health hazards. This review contributes to the broader discourse on food safety, environmental toxicology, and sustainable agricultural practices.